FACTORS INFLUENCINGPATIENT SATISFACTIONA SYSTEMATIC REVIEW - Zakaria, Edwin (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Along with the progress of time, hospital as service provider is required to provide better services. The challange for hospitals is to fulfill the expectations of society for better health care. Patient satisfaction is a comparison between the perceptions care received by expectations before getting treatment. Aims: This is to evaluate patient satisfaction as an effort to see the levelof success of the hospital. Methods: The method was a systematic review by using the search facility online. Only research in english language and describe factors that influence patient satisfaction is maintained. The results of this study were 565 journals found at early stage and at the end we found 7 journals in review. Results: The purpose of research is to describe the level of satisfaction of hospital. all the four items namely performance of housekeeping staff, operational x-ray facilities, maintenance of file records and transparent billing procedure are significant in predicting satisfaction towards internal facilities provided in the hospitals. Conclusion: Overall, on the articles reviewed accepted that all the patient satisfaction dimensions positively and significantly contribute towards patient satisfaction which also acts as an important mediating factor between dimensions and loyalty.Â